Crystallization: A Novel Acoustomicrofluidic Nebulization Technique Yielding New Crystallization Morphologies (Adv. Mater. 3/2018). Issue 3 (15th January 2018) - Ahmed, Heba; Lee, Lillian; Darmanin, Connie; Yeo, Leslie Y.
Abstract : New crystal morphologies, previously undiscovered, for both organic and inorganic materials are obtained by Leslie Y. Yeo and co‐workers, as discussed in article number 1602040, as a consequence of the unique intermediate evaporation rate regime to which aerosol droplets, generated from a microfluidic nebulization platform utilizing a recently discovered novel class of hybrid surface and bulk acoustic waves, are subjected.